2023
DOI: 10.3390/en16124679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Lignocellulosic Biomass-Derived Polyoxymethylene Dimethyl Ether as a Sustainable Fuel for Internal Combustion Engines

Abstract: The most effective way to reduce internal combustion engine emissions is to use a sustainable alternative fuel that contains oxygen molecules. Alternative fuels may be used to address a future global energy crisis. Different oxygenated alternative fuels have been investigated in internal combustion engines. Polyoxymethylene di-methylene ether (PODE), which contains 3–5 CH2O groups, is currently superior in the field of oxygenated fuels due to its physical and chemical properties. Furthermore, using PODE as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Heavy-duty vehicles for road transport use compression ignition engines, and among the many promising diesel alternatives [12][13][14], OME is one of the most investigated. Regarding current research activities, the authors of [15] analyzed the origin and number of papers published on OME and found that extensive research began after 2015; nowadays, the interest is still ongoing. The top three countries that lead the research in this field are China, the US, and the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy-duty vehicles for road transport use compression ignition engines, and among the many promising diesel alternatives [12][13][14], OME is one of the most investigated. Regarding current research activities, the authors of [15] analyzed the origin and number of papers published on OME and found that extensive research began after 2015; nowadays, the interest is still ongoing. The top three countries that lead the research in this field are China, the US, and the UK.…”
Section: Introductionmentioning
confidence: 99%